2017
DOI: 10.3389/fgene.2017.00099
|View full text |Cite
|
Sign up to set email alerts
|

Social and Communicative Functions of Informed Consent Forms in East Asia and Beyond

Abstract: The recent research and technology development in medical genomics has raised new issues that are profoundly different from those encountered in traditional clinical research for which informed consent was developed. Global initiatives for international collaboration and public participation in genomics research now face an increasing demand for new forms of informed consent which reflect local contexts. This article analyzes informed consent forms (ICFs) for genomic research formulated by four selected resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 88 publications
(93 reference statements)
0
9
0
Order By: Relevance
“…Some groups have different views as to who can appropriately provide consent, which may diverge from the Western individualist notion of autonomous decision-making. Collective (family or community) engagement, recruitment, and consent has been utilized in settings including some indigenous communities [e.g., Australia, New Zealand, and Alaska ( 29 )], southern Africa ( 28 ), and East Asia ( 31 33 ). Where research focuses on a specific community, the International Society for Biological and Environmental Repositories endorses community participation in planning for the study and consent processes, specimen use and dissemination of research findings ( 34 ).…”
Section: Recognized Barriers To Participationmentioning
confidence: 99%
“…Some groups have different views as to who can appropriately provide consent, which may diverge from the Western individualist notion of autonomous decision-making. Collective (family or community) engagement, recruitment, and consent has been utilized in settings including some indigenous communities [e.g., Australia, New Zealand, and Alaska ( 29 )], southern Africa ( 28 ), and East Asia ( 31 33 ). Where research focuses on a specific community, the International Society for Biological and Environmental Repositories endorses community participation in planning for the study and consent processes, specimen use and dissemination of research findings ( 34 ).…”
Section: Recognized Barriers To Participationmentioning
confidence: 99%
“…However, as emerging biotechnologies have a broad influence on many facets of society, it has become more important to assess the social implications by conducting research to identify public attitudes regarding the early phase technology development (Guston and Sarewitz, 2002). Despite the current established regulations and agreements, certain ethical, legal, and social issues need to be addressed to reflect regional, national, and global contexts (Yoshizawa et al, 2014(Yoshizawa et al, , 2017Minari et al, 2018). Particularly, it is controversial how to practically apply germline genome editing for humans and the natural environment.…”
Section: Introductionmentioning
confidence: 99%
“…Issues surrounding consent in the context of the globalisation of biobanks are made more complex by differences in values across different cultures. For example, an analysis of consent forms in East Asia found that they performed a broader social and communicative function than comparable documents from genomic research projects in Europe, the UK and Africa (Yoshizawa et al 2017). This reflects earlier findings that in East Asian countries, informed consent is more of a collective process than an individual one (Yoshizawa et al 2014), with significant involvement of participants' family and community members in the decision making process.…”
Section: Consentmentioning
confidence: 64%
“…Another consideration is that the imposition of UK standards for safeguarding patient data leads to a more individualistic emphasis on participant rights. This does not necessarily align with the tendency of East Asian countries to emphasise the broader societal benefits of participating in genomic research (Yoshizawa et al 2017).…”
Section: Privacy and Confidentialitymentioning
confidence: 93%
See 1 more Smart Citation